YANALIL (Yasin dan Tahlil) : Wujud Ekspresi NU Sebagai Resiliensi Masyarakat Pekalongan Dalam Mempertahankan Manhaj Aswaja Dan Ideologi Bangsa Indonesia - Fidiyah Sari (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2023)
Yanalil is an abbreviation of Yasin and Tahlil is a tradition of Muslims, especially the Nahdlatul Ulama (NU) community in Indonesia, which has become routine ingrained. Yanalil is an expression of community resilience. This is because through Yanalil the NU community can express their resilience or resilience in facing life's challenges, for example the death of their family through kenduren. This type of research uses a qualitative approach with data collection techniques using library research. Yanalil was able to defend the manhaj aswaja because the recitation of yanalil did not come out of the Qur'an and Hadith properly and correctly. Apart from referring to the Al-Qur'an and Hadith, Yanalil also holds the values ??that form the basis of aspects of the social life of the Indonesian people which are listed in Pancasila as the ideology of the Indonesian nation. Keywords: Yasin and Tahlil, NU expressions, community resilience, manhaj aswaja, ideology of the Indonesian nation